Mild oxidation of alcohols with o-iodoxybenzoic acid (IBX) in a water/CH2CL2mixture in the presence of phase-transfer catalyst - Chutima Kuhakarn (2018)
A mild oxidation of alcohols to the respective carbonyl compounds with o-iodoxybenzoic acid (IBX) catalyzed by n-Bu4NBr in a water/dichloromethane (1:1) mixture is described. The method offers the advantage of a simple, inexpensive catalyst and the diminution of organic solvent employed in the reaction. Copyright © Taylor & Francis Group, LLC.